PERBANDINGAN METODE BALANCED SCORECARD DAN NAÏVE BAYES DALAM PREDIKSI DAN REKOMENDASI PADA PENILAIAN KINERJA GURU (STUDI KASUS : SMK YADIKA 12 DEPOK) - Kurniawan, Zaqi; Indra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Teacher Performance Assessment guarantees a quality learning process at all levels of education. Educational supervision will be carried out with the aim to improve the quality of teaching / teacher so that the competitiveness of students studying at the school will increase towards a better direction. Supervision assessment is a class visit technique to obtain data about the actual situation regarding the ability and skills of teachers in teaching and mastery of class. To determine the teacher's performance, one approach can be done using the Balanced Scorecard approach and Naïve Bayes classification. The determination of teacher performance is then processed using Analytic Network Process-based modeling to improve teacher evaluation criteria that are still low. With the help of Super Decision software, a decision support system was created in determining teacher performance. The results of this study are the recommendations of permanent teachers in Junior High Schools, High Schools, and Vocational Schools Yadika 12 Depok based on performance to be objective and make more efficient decisions.